Polyphenols from halophytes and modified atmosphere packaging improve sensorial and biochemical markers of quality of common dolphinfish (Coryphaena hippurus) fillets. Issue 5 (30th March 2016) - Messina, Concetta Maria; Bono, Gioacchino; Arena, Rosaria; Randazzo, Mariano; Manuguerra, Simona; Santulli, Andrea
Abstract: Quality and shelf‐life of whole and filleted Coryphaena hippurus, stored with modified atmosphere packaging (MAP) and natural antioxidants from halophytes (HAL), were investigated. Fillets were divided into control, simply sealed in trays; MAP, preserved by modified atmosphere (45% CO2, 50% N2, 5% O2 ); and MAP‐HAL, pretreated with antioxidants and preserved by MAP. Whole and filleted fish were stored at −1 ± 0.5°C for 18 days. The quality of the samples was analyzed at the time of packaging and after 3, 6, 9, 12, 15, and 18 days. The MAP and MAP‐HAL groups maintained the best sensorial profile, pH, and drip loss with respect to the untreated fillets. Higher levels of total volatile basic nitrogen (TVB‐N) and oxidized proteins were observed in untreated samples with respect to the MAP and MAP‐HAL groups. The principle component analysis revealed a different quality profile for untreated and MAP‐treated fish. Abstract : In this study, we describe the effects of MAP and antioxidants in extending shelf‐life of dolphinfish, ameliorating both sensorial, chemical, and biochemical markers of quality.